Investigating strategies for addressing child and adolescent mental health following exposure to extreme weather events in low- and middle-income countries: A scoping review - Kadota, Molly Kaelin (Department of Public Health and Family Medicine, 2023)
The inevitability of an increase in extreme weather events (EWE) due to climate change will likely influence every determinant of human health and wellbeing. Children and adolescents, defined as anyone under the age of 19, are among the most susceptible because of their unique vulnerabilities (i.e. physiologically, developmentally, biologically, and behaviourally) and lifespans. The effects on physical health are generally well documented, and many climate change adaptation strategies have begun to include them in their considerations. However, the implications of EWE exposure on mental health are less understood, particularly within low- and middle-income countries (LMICs). Populations residing in LMICs are especially vulnerable because of pre-existing conditions like already extreme weather, lack of resources, poor economic conditions, weak health systems, high burden of disease, and poor governance. Therefore, children and adolescents in LMICs maintain a heightened vulnerability to experiencing adverse effects. In Part A, a preliminary literature review determined the breadth of information documenting child and adolescent mental health outcomes following exposure to EWE. Research, mainly from high-income countries (HICs) or international organisations, demonstrating an association between mental health impacts and climate change, focused primarily on adult populations, has increased substantially over the last few years. Experiencing an EWE in childhood or adolescence likely leads to direct (e.g. anxiety, post-traumatic stress disorder, depression, behavioural disorders, and suicidal ideations), indirect (e.g. displacement, loss of sense of place, violence, malnutrition, developmental delays, and disruption of education), and overarching (e.g. general climate anxiety about impending threats) mental health impacts, presenting in both the short- and long-term. The goals of adaptation and mitigation strategies were also presented in the protocol to determine the potential for specific mental health strategies. In Part B, then, a scoping review was conducted to provide a narrative of where adaptation, resilience, and mitigation strategies in LMICs address, and where they do not, child and adolescent mental health impacts following exposures to EWE. A search conducted in June-August 2021 of 12 online databases from the Pubmed, EBSCOhost, and Scopus platforms and grey literature sites like Google Scholar, Microsoft Academic, and NGO pages identified 5,073 relevant records. Search results were limited to documents written in English and filtered by a 2000-2021 date range. In the current LMICs climate change strategies, the review highlighted a general lack of consideration for child and adolescent mental health and resilience. Therefore, eight main themes recurring in the literature were identified as integral components for including child and adolescent mental health in future national strategies and policymaking discussions. The themes provide general guidance, but their addition necessitates country-specific conceptualisation to determine technical considerations (e.g. funding and responsibility) and relevance. This review, therefore, emphasised the necessity for LMICs to begin including child and adolescent mental health in climate change strategies, highlighted key recommendations that were applicable in the LMICs context, and illuminated still existing gaps in the literature and potential areas for future research.